Mucosal Interactions between Genetics, Diet, and Microbiome in Inflammatory Bowel Disease - Basson, Abigail; Trotter, Ashley; Rodriguez-Palacios, Alex; Cominelli, Fabio (Frontiers in Immunology, 2016)
Numerous reviews have discussed gut microbiota composition changes during inflammatory bowel diseases (IBD), particularly Crohn’s disease (CD). However, most studies address the observed effects by focusing on studying the univariate connection between disease and dietary-induced alterations to gut microbiota composition. The possibility that these effects may reflect a number of other interconnected (i.e. pantropic) mechanisms, activated in parallel, particularly concerning various bacterial metabolites, is in the process of been elucidated. Progress seems however hampered by various difficult-to-study factors interacting at the mucosal level. Here we highlight some of such factors that merit consideration, namely; 1) the contribution of host genetics and diet in altering gut microbiome, and in turn, the crosstalk among secondary metabolic pathways; 2) the interdependence between the amount of dietary fat, the fatty acid composition, the effects of timing and route of administration on gut microbiota community, and the impact of microbiota-derived fatty acids; 3) the effect of diet on bile acid composition, and the modulator role of bile acids on the gut microbiota; 4) the impact of endogenous and exogenous intestinal micronutrients and metabolites, and 5) the need to consider food associated toxins and chemicals which can introduce confounding immune modulating elements (e.g., antioxidant and phytochemicals in oils and proteins). These concepts, which are not mutually exclusive, are herein illustrated paying special emphasis on physiologically inter-related processes.